Pemikiran Teologis Terhadap Krisis Iklim: Tanggapan Dan Tantangan Dalam Membangun Ketahanan Ekologi (Jurnal Pendidikan Agama dan Teologi, 2024)
The global climate crisis has become one of the greatest challenges facing humanity today. This phenomenon not only has an impact on the natural environment, but also affects social, economic and spiritual life. In this context, theological thinking has an important role in shaping responses and solutions to the climate crisis. This article explores how various religious traditions interpret and respond to the climate crisis, as well as the challenges faced in building ecological resilience. By examining theological perspectives from major traditions, this article seeks to provide new insights into facing these increasingly pressing environmental challenges.